Gene Environment Interactions in the Etiology of Neural Tube Defects - Finnell, Richard H.; Caiaffa, Carlo Donato; Kim, Sung-Eun; Lei, Yunping; Steele, John; Cao, Xuanye; Tukeman, Gabriel; Lin, Ying Linda; Cabrera, Robert M.; Wlodarczyk, Bogdan J. (Frontiers in Genetics, 2021)
Human structural congenital malformations are the leading cause of infant mortality in the United States. Estimates from the United States Center for Disease Control and Prevention (CDC) determine that close to 3% of all United States newborns present with birth defects; the worldwide estimate approaches 6% of infants presenting with congenital anomalies. The scientific community has recognized for decades that the majority of birth defects have undetermined etiologies, although we propose that environmental agents interacting with inherited susceptibility genes are the major contributing factors. Neural tube defects (NTDs) are among the most prevalent human birth defects and as such, these malformations will be the primary focus of this review. NTDs result from failures in embryonic central nervous system development and are classified by their anatomical locations. Defects in the posterior portion of the neural tube are referred to as meningomyeloceles (spina bifida), while the more anterior defects are differentiated as anencephaly, encephalocele, or iniencephaly. Craniorachischisis involves a failure of the neural folds to elevate and thus disrupt the entire length of the neural tube. Worldwide NTDs have a prevalence of approximately 18.6 per 10,000 live births. It is widely believed that genetic factors are responsible for some 70% of NTDs, while the intrauterine environment tips the balance toward neurulation failure in at risk individuals. Despite aggressive educational campaigns to inform the public about folic acid supplementation and the benefits of providing mandatory folic acid food fortification in the United States, NTDs still affect up to 2,300 United States births annually and some 166,000 spina bifida patients currently live in the United States, more than half of whom are now adults. Within the context of this review, we will consider the role of maternal nutritional status (deficiency states involving B vitamins and one carbon analytes) and the potential modifiers of NTD risk beyond folic acid. There are several well-established human teratogens that contribute to the population burden of NTDs, including: industrial waste and pollutants [e.g., arsenic, pesticides, and polycyclic aromatic hydrocarbons (PAHs)], pharmaceuticals (e.g., anti-epileptic medications), and maternal hyperthermia during the first trimester. Animal models for these teratogens are described with attention focused on valproic acid (VPA; Depakote). Genetic interrogation of model systems involving VPA will be used as a model approach to discerning susceptibility factors that define the gene-environment interactions contributing to the etiology of NTDs.